Effectiveness Of Endhorpin Massage On The Success Of Labor Induction - Reka Safitri; Wahyu Pujiastuti; Bekti Yuniyanti (Poltekkes Kemenkes Semarang, 2022)
Background: Indications of labor induction is main cause maternal mortality in Central Java. Misoprostol can be used for labor induction with success rate of 46%. Besides, endorphin massage was also used to improve the success of misoprostol induction. Endorphin massage could increase endorphin and oxytocin secretion. Thus, the purpose of this study was to determine the effectiveness of endorphin massage on the success of induction. Methods: This study was carried out by quantitative design with quasi-experimental design and non-equivalent control group pretest post-test design. The population of this study were pregnancy women with misoprostol induction at RSUD Dr. Soedirman Kebumen that collected between January 17th to February 17th 2022, as many as 30 respondents. The participants were divided into two groups, the experimental group, which were given misoprostol induction with endorphin massage, and the control group, which were given misoprostol induction without endorphin massage. Bishop score alteration observation for misoprostol induction success was in 6 hours since misoprostol induction was given to the patient Results: The results of Wilcoxon Signed Rank Test showed significant difference in the bishop score before after the induction with endorphin massage (p=0.001;p